2005
DOI: 10.1093/occmed/kqi152
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, management and impact of urinary incontinence in the workplace

Abstract: Urinary incontinence is prevalent among employed women. Those who experience severe symptoms report that it has a negative effect on aspects of work. Programs on the prevalence and impact of urinary incontinence would help educate both employers and employees, and may lead to the development of better management techniques in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
98
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 23 publications
(26 reference statements)
4
98
0
4
Order By: Relevance
“…W badaniach Fultz i wsp. wykazano incydenty wycieku moczu o charakterze wysiłkowym u 52% badanych kobiet potwierdzających objawy nietrzymania moczu [17].…”
Section: Dyskusjaunclassified
“…W badaniach Fultz i wsp. wykazano incydenty wycieku moczu o charakterze wysiłkowym u 52% badanych kobiet potwierdzających objawy nietrzymania moczu [17].…”
Section: Dyskusjaunclassified
“…11 Considering separately the types of urinary incontinence, Fultz et al found 52% of SUI, 10% of UUI, 37% of mixed UI, and 2% of other types. 6 A study conducted with 400 women showed quite different results: 18.3% had SUI, 17.5% had UUI, and 39.5% had mixed UI. 12 In a study conducted in 1997, the authors interviewed 410 women and found that 12.6% of those with incontinence had SUI.…”
Section: Introductionmentioning
confidence: 97%
“…5 Fultz et al assessed the impact of UI in 3,364 employed women and demonstrated impairment of work rhythm because of increased frequency of bathroom breaks. 6 Tamanini et al, using the International Consultation on Incontinence Questionnaire (ICIQ-SF), showed that among 225 patients with UI, 8.9% (20) and 17.8% (40) considered the impact of this condition on their quality of life to be severe and very severe, respectively. 7 Telephone interviews conducted in 2003 with 82,196 people over 65 years demonstrated that the prevalence of UI is twice as high in women compared to men and UI is significantly associated with depression.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 5 years at least 12 epidemiological studies of the prevalence of urinary incontinence have been done in the United States. In 9 studies performed with women we find very different results ranging between 15% with Latin women over 65 years old (Espino, Palmer et al 2003), 18% with Asiatic women (Huang, Thom et al 2006), and up to 40% with noninstitutionalized women (Fultz, Girts et al 2005;Melville, Katon et al 2005;Minassian, Stewart et al 2008). In Spain, epidemiological studies before 2003 show a prevalence of nearly 40% in women over 65 years old, but in later studies the amount was under 35.1% in persons over 64 years, 23% in women over 18 years old, 20% in working women and 14% in women between 40 and 64 years old (Martínez-Agulló, Ruiz-Cerdá et al 2009).…”
mentioning
confidence: 94%